Effect of Promoter Methylation on the Expression of Porcine MUC2 Gene and Resistance to PEDV Infection - Xiao, Yeyi; Zhou, Yajing; Sun, Shouyong; Wang, Haifei; Wu, Shenglong; Bao, Wenbin (Frontiers in Veterinary Science, 2021)
Integrity of the intestinal mucosal barrier is closely reliated to the occurrence of diarrhea. As an important component protein of the intestinal mucosal barrier, Mucin 2 (MUC2) plays a critical role in preventing the invasion of pathogens, toxins, and foreign bodies. In the present study, we preliminaries verified the function of the porcine MUC2 gene in resisting porcine epidemic diarrhea virus (PEDV) infection and investigated the effect of DNA methylation in the promoter region on MUC2 gene expression. The results showed that after PEDV infection, the intestinal mucosal barrier was damaged. Moreover, MUC2 expression was significantly higher in PEDV-infected piglets than in healthy piglets (P < 0.01). The mRNA expression of MUC2 was significantly higher in PEDV-infected IPEC-J2 cells than in non-infected IPEC-J2 cells (P < 0.05). Methylation of the mC-5 site in the MUC2 promoter inhibited the binding of Yin Yang 1 (YY1) to the promoter. Thereby inhibiting the expression of MUC2 and increasing the susceptibility of piglets to PEDV. In conclusion, this study suggests that MUC2 plays an essential regulatory role in PEDV infection. High MUC2 expression benefits improving the resistance of pigs to PEDV infection. The binding of YY1 to the MUC2 promoter is hindered by the methylation of the mC-5 site, which downregulates MUC2 expression and ultimately affects the resistance of pigs to PEDV infection.